Negative electron affinity opens quantum well in MgO layers on Ag(100). (5th November 2021) - Helmreich, Rebecca; Classen, Andrej; Fauster, Thomas
Abstract: Epitaxial MgO films on Ag(100) were studied by photoelectron spectroscopy. From the low-energy part of the spectra we obtain a negative electron affinity of about −0.9 eV. Even though electrons in the lowest conduction band are not confined by a potential barrier at the surface, quantum-well resonances are observed. The dispersion of the conduction band is determined in good agreement with theoretical calculations. Aspects of observing image-potential states predicted by theory on MgO films are discussed.